Sistema jagunço: alegoria benjaminiana de um estado de exceção em Grande sertão: veredas - Saraiva, Aline Crispino Pessôa (2023)
The thematic plurality and the multiplicity of meanings inherent to the elements of the narrative, present in Grande sertão: veredas, enable proposals for reading this novel under different approaches. This dissertation, through an interdisciplinary perspective, aims to analyze the jagunço system, the central aspect of the plot, as a possible allegorical representation of a state of exception. This apprehension is based on the conceptions about allegory developed by Walter Benjamin in his book Origin of German tragic drama, highlighting the existing points of convergence between the lectures of the German theorist and the literary composition of Guimarães Rosa. From such intersections, significant aspects relevant to the trajectory of the protagonist Riobaldo are identified, in the midst of jagunçagem, which reflect the experience concerning the suspension of a normative order in the face of the aforementioned legal institute. In this perspective, the collaborative potential of correspondences between literature and law stands out, which provide differentiated dialogical forms of perception, questioning, understanding and reflection about human relations